PENGHILANGAN WARNA COKLAT LARUTAN GULA STEVIA MENGGUNAKAN KARBON AKTIF - Ibrahim Ghazi; Bayu Wicaksono; Abdullah Abdullah (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
At this time there is many prospecting ofalternative natural sweetener that has a high level of sweetness, low in calories and not carcinogenic. One of those is the natural sweetener stevia from the leaves of the stevia plant. One of the method to get the sweetener is byextracting the stevia leaf. However, after the process of extraction the solution turns brown due to tannins that contained in the stevia leaf. Oneof the processto eliminate tanninfrom the solution is by using activated carbon to absorb tannins. Materials used in this research is dried stevia leaves, water, activated carbon, and citric acid. Then equipments used is beaker glass, pipette, measuring glass, magnetic stirrer, heater, pH meter, filter paper, scale, and spectrophotometer. Extraction process used 65oC of temperature, 300 rpm of stirring speed for 10 minutes. Adsorption processdid at room temperature within 24 hours. After adsorption process each sample will be analyze with spectrophotometer using 725 nm of wavelength to get the amount of tannin contained. The result of this research is the higher pH operation that used the smaller tannin that contained. Then the lower temperature that used to heated the adsorbent the smaller tannin that contained. The optimum conditiom for tannin adsorption based on this research is using 200 oC of temperature to heated the adsorbent and using 6 of pH operation.